Single CpG island methylation is not sufficient to maintain the silenced expression of CASPASE-8 apoptosis-related gene among women with epithelial ovarian cancer - Braga, Leticia da Conceicao [UNESP]; Silva, Luciana Maria; Alvares da Silva Ramos, Ana Paula; Piedade, Josiane Barbosa; Teixeira Vidigal, Paula Vieira; Traiman, Paulo [UNESP]; Silva Filho, Agnaldo Lopes da [UNESP] (Elsevier B.V., 2014)
Despite impressive research efforts, the biology of epithelial ovarian cancer (EOC) remains poorly understood and alterations in the expression of CASPASE-8 contribute to a worse tumor prognosis. This study assesses the methylation of the CpG island within the CASPASE-8 promoter and CASPASE-8 gene expression both in cystadenoma tumors and in primary and metastatic EOC. DNA and RNA were obtained from women with normal ovarian tissues (n = 18), ovarian serous cystadenoma tumors (n = 11) and EOC (n = 16) using Trizol (R). The methylation frequency of the CpG island in the CASPASE-8 promoter was assessed using the methylation-specific PCR assay after DNA bisulfite conversion. Quantitative PCR was performed to quantify the relative levels of CASPASE-8 in each sample. The differences between samples with each group were evaluated using the Mann-Whitney U and Kruskal-Wallis tests as indicated. Hemimethylation of the CASPASE-8 promoter was found in 11.8% of the normal ovary samples, 20% of the cystadenoma tumors and 20% of the metastatic EOC, while methylation of the CASPASE-8 promoter was absent in the EOC primary tissues (P = 0.047). An increased CASPASE-8 expression level was observed in all tumor groups. Significant differences were observed in the CASPASE-8 expression levels when compared with all ovarian tumor groups (P = 0.0278). Promoter DNA methylation did not associate with expression levels of CASPASE-8, suggesting the presence of other mechanisms in relation to gene expression control in EOC; thus providing a better understanding of this complex disease. (C) 2013 Elsevier Masson SAS. All rights reserved.
Keywords: Epithelial ovarian cancer; CASPASE-8; Expression